Long-term results after modified Burton-Pellegrini’s technique in 24 cases affected by advanced rhizarthrosis. - Pogliacomi, Francesco; Oldani, Danila; Schiavi, Paolo; Pedrazzini, Alessio; Vaienti, Enrico; Calderazzi, Filippo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Rhizarthrosis common in elderly and represents 10% of all artrhitic manifestations. Trapeziectomy with ligament reconstruction and tendon interposition remains the gold standard for stages II to IV according to Eaton and Littler. This retrospective study aimed to evaluate the results of 24 patients affected by advanced rhizarthrosis who underwent to modified Burton-Pellegrini’s trapeziectomy with ligamentoplasty using the entire flexor carpi radialis tendon.Methods: Patients were assessed through DASH and PRWHE questionnaires; the examination focused also on pain symptoms (VAS score) and the results obtained in carrying out specific tests to evaluate the trapezius-metacarpal functionality (key-pinch, grip strength, Kapandji test, reduction of wrist flexion). Furthermore, postoperative complications were evaluated.Results: Clinical evaluation and individual satisfaction were positive in most cases (mean DASH 18,8 and mean PRWHE 21,7). VAS pain score reduced of 76.7%, grip strength and key pinch were similar to those of the non-operated hand and Kapandji test was excellent in 20 patients.  One superficial wound infection was encountered which resolved by specific antibiotic therapy.Conclusions: The choice of the most appropriate treatment depends on clinical conditions and socio-occupational factors of the patient (age, sex and functional needs), the degree of osteoarthritis and the presence of deformaties of the first metacarpophalangeal joint. Surgery aims to relief pain and to improve joint function and strength. According to the results observed this surgical technique has to be considered a valid option for the treatment of advanced rhizarthrosis as it provides pain relief, stability and mobility of the thumb.